2021
DOI: 10.1371/journal.pone.0256730
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of electric cigarette liquid effect on mouse brain tumor growth through EGFR and ERK activation

Abstract: Introduction Recently, electric cigarettes with liquid (e-liquid) were introduced as an alternative to tobacco smoking. They were promoted as possible cessation aids and were considered to be potentially less harmful than traditional tobacco-based cigarettes. However, there is little information on the toxicants present in e-liquids and their possible carcinogenic effects. Methods Western blot analysis was performed to identify the protein levels of cancer progression related signal transducers. Patient-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The overexpression ranges from 43% to 89% in non-small cell lung cancer [ 121 ]. It has been reported that patient-derived glioblastoma stem-like cells exposed to e-liquids showed an increased level of phospho-EGFR, leading to autophagy deficiency and to the activation of ERK [ 122 , 123 ]. In addition, in vivo studies showed that the injection of patient-derived brain tumor cells into mice brains accelerated tumor growth and the poor prognosis in the e-liquid-treated group compared to the control group [ 94 , 95 ].…”
Section: Metals and Molecular Carcinogenesismentioning
confidence: 99%
“…The overexpression ranges from 43% to 89% in non-small cell lung cancer [ 121 ]. It has been reported that patient-derived glioblastoma stem-like cells exposed to e-liquids showed an increased level of phospho-EGFR, leading to autophagy deficiency and to the activation of ERK [ 122 , 123 ]. In addition, in vivo studies showed that the injection of patient-derived brain tumor cells into mice brains accelerated tumor growth and the poor prognosis in the e-liquid-treated group compared to the control group [ 94 , 95 ].…”
Section: Metals and Molecular Carcinogenesismentioning
confidence: 99%
“…Carcinogenic and tumour promoting properties of e-cigarettes were also reported. E-cigarette exposure acted as a lung carcinogen and a potential bladder carcinogen in mice and mouse xenografts from patient-derived brain tumour treated with e-cigarette liquid had accelerated growth and worse prognosis compared to the control group [28,29]. Exposure to e-cigarettes was found to increase cisplatin resistance in oral cancer cells, indicating their role in therapy-resistance in cancer as well [30].…”
Section: Introductionmentioning
confidence: 96%